GROWTH AND YIELD OF Asystasia gangetica AT DIFFERENT GROUND WATER LEVELS - M. D., Fahrezy; Wirawan, I W.; Trisnadewi, A. A. A. S (Jurnal Peternakan Tropika, 2023)
Water is a limiting factor that affects plant growth. Water requirement for plants depends on the type of plant and its growth phase. This study aimed to determine the growth and the yield of Asystasia gangetica at different groundwater levels. This study has been done in a greenhouse, Sesetan Research Station, Animal Husbandry Faculty, Udayana University on Markisa Alley of Sesetan Street for 12 weeks, using a completely randomized design (CRD) with four treatments and seven replications so that there are 28 experimental units. The treatment given was the level of water soil which consisted of: 40% field capacity (FC), 60% FC, 80% FC, and 100% FC. The variables observed were growth variables, yield variables and growth characteristics variables. The results showed that the growth and yield of Asystasia gangetica on100% FC resulted the highest on plant height of 42.21 cm, number of leaves of 119.86 pieces and number of branches of 21.86 bar between all treatments.Treatment 100% FC is the higest total dry weight of forage with average 7.59 g, and treatment 40% FC is the highest on ratio of total dry weight of forage to dry weight of roots with average 1.39 g. It could be concluded that growth and yield of Asystasia gangetica were increasing with the increasing level of water soil and the highest is 100% FC.   Key words: water soil level, Asystasia gangetica, growth, yiel